The Effect of Hydro Power on the Optimal Distribution of Wind and Solar Generation Facilities in a Simplified Highly Renewable European Power System. (November 2016) - Kies, Alexander; Schyska, Bruno U.; von Bremen, Lueder
Abstract: We investigate the optimal distribution of wind and photovoltaic generation facilities in Europe. For this purpose, feed-in data covering Europe for the renewable sources wind, photovoltaics and hydro are used. Together with historical load data and a transmission model, a simplified European power system is simulated. The results show that wind should be placed in countries on the shores of the North-Sea while the picture for PV is complex: A band from Germany to Italy over Switzerland is optimal. Furthermore, we show that hydro power has little influence on the optimal distribution.